High-Performance Cementitious Matrix using Carbon Nanofibers - Muhammad Maqbool Sadiq Awan; Parviz Soroushian; Arshad Ali; Muhammad Yousaf Saqid Awan (Indonesian Journal of Science and Technology, 2017)
Graphite nanomaterials would realize their reinforcement potential within cement-based materials when they are thoroughly dispersed and effectively bonded to cement hydrates. Thorough dispersion of graphite nanomaterials in the fresh cementitious matrix encounters challenges associated with the hydrophobic nature of nanomaterial surfaces and their strong tendency towards agglomeration via attractive van der Waals forces. Effective interfacial interactions with cement hydrates are further challenged by the relatively inert nature of nanomaterial surfaces. An experimental program was conducted with the objective of effectively utilizing both acid-oxidized and pristine carbon nanofibers towards reinforcement of high-performance cementitious pastes. Hybrid reinforcement systems comprising optimum volume fraction of carbon nanofibers and micro-scale fibers were also evaluated in cementitious matrices. The improvements in nanofiber dispersion and interfacial interactions resulting from acid-oxidation and use of proper dispersion techniques were found to bring about significant gains in the engineering properties of high-performance cementitious materials.